Carbon Dots with Dual‐Emissive, Robust, and Aggregation‐Induced Room‐Temperature Phosphorescence Characteristics. Issue 3 (5th December 2019) - Jiang, Kai; Gao, Xiaolu; Feng, Xiangyu; Wang, Yuhui; Li, Zhongjun; Lin, Hengwei
Abstract: Carbon dots (CDs) with dual‐emissive, robust, and aggregation‐induced RTP characteristics are reported for the first time. The TA‐CDs are prepared via hydrothermal treatment of trimellitic acid and exhibit unique white prompt and yellow RTP emissions in solid state under UV excitation (365 nm) on and off, respectively. The yellow RTP emission of TA‐CDs powder should be resulted from the formation of a new excited triplet state due to their aggregation, and the white prompt emission is due to their blue fluorescence and yellow RTP dual‐emissive nature. The RTP emission of TA‐CDs powder was highly stable under grinding, which is very rare amongst traditional pure organic RTP materials. To employ the unique characteristics of TA‐CDs, advanced anti‐counterfeiting and information encryption methodologies (water‐stimuli‐response producing RTP) were preliminarily investigated. Abstract : Carbon dots (CDs) with dual‐emissive, robust, and aggregation‐induced room‐temperature phosphorescence (RTP) characteristics are reported. Potential applications of the as‐prepared CDs in advanced anti‐counterfeit and information encryption are also demonstrated.